Plays that Make Policy: A Debwewin Journey Through Legislative Theatre - Majaury, Heather (University of Guelph, 2013)
Answering Augusto Boal’s call for further explorations of Legislative Theatre, this thesis asks how Canadian Legislative projects have contributed to our understanding of “theatre as politics” over and above the original Rio mandate. Utilizing a distinctly Anishinabe research methodology, I reflect upon my own practice as a Theatre of the Oppressed Joker from an Indigenous epistemological perspective. This thesis searches for how Legislative Theatre could be useful within the public education system, First Nations and Canadian state/settler relationships and negotiations, within municipal government, community-based organizations, and grassroots social justice initiatives. I conclude that Legislative Theatre is an innovative think tank methodology that potentially balances expert knowledge and experiential knowledge in respectful partnership. “Plays that make Policy” counter hegemonic forces using the performing arts. For Legislative Theatre to intervene successfully in law making it must empower citizenry to work with listening government. Therefore it requires cross-sectorial institutionalization to thrive.